1986
DOI: 10.1017/s0003356100017918
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a combined androgenic-oestrogenic anabolic agent in steers and bulls 1. Growth and carcass composition

Abstract: Twenty-one pairs of male cattle twins, 10 of which were monozygotic, were used in a study of the effects of a combined implant of trenbolone acetate (140 mg) and oestradiol-17B (20 mg) on growth and carcass composition. There were three comparisons within pairs: (1) between bulls and steers (no implants); (2) between bulls and implanted steers; and (3) between bulls and implanted bulls.Implants were given twice, at 44 to 73 days and at 300 days of age. Animals were slaughtered at 400 days following recorded co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…When the propensity to deposit fat during growth was reduced the pigs were able to achieve their target for protein deposition at a lower food intake. These findings and those of Fisher et al (1986) are entirely consistent with my general hypothesis, although they do not exclude alternative explanations.…”
Section: Varying Physiological Statesupporting
confidence: 86%
See 2 more Smart Citations
“…When the propensity to deposit fat during growth was reduced the pigs were able to achieve their target for protein deposition at a lower food intake. These findings and those of Fisher et al (1986) are entirely consistent with my general hypothesis, although they do not exclude alternative explanations.…”
Section: Varying Physiological Statesupporting
confidence: 86%
“…' Fisher et al (1986) have measured effects of castration and implantation with anabolic steroids on appetite and growth in twin cattle. Implanted castrate males achieved a lean tissue growth rate approximately halfway between that of castrate and entire males but deposited fat at the same rate as castrates.…”
Section: Varying Physiological Statementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Silcox et al (1986) found that bulls implanted with Z or Z plus TBA were similar to NIB in marbling. However, Fisher et al (1986b) reported that bulls implanted with TBA plus estradiol had more marbling than NIB, whereas IS seemed to have less marbling.…”
Section: Results and Dlscusslonmentioning
confidence: 97%
“…However, because the implanted steer yielded a greater weight of lean tissue and was relatively more efficient at doing so (Fisher et al, 1986b), the next result was that implantation of the steer was economically advantageous. Fatty tissues were not so responsive to implantation.…”
Section: Carcass Valuementioning
confidence: 99%